Role of p53 codon 72 polymorphism in chromosomal aberrations and mitotic index in patients with chronic hepatitis B - Akbaş, H.; Yalcin, K.; Isi, H.; Tekes, S.; Atay, A.E.; Akkus, Z.; Budak, T. (Brazilian journal of medical and biological research, 2012)
Polymorphisms of the p53 gene, which participates in DNA repair, can affect the functioning of the p53 protein. The Arg and Pro variants in p53 codon 72 were shown to have different regulation properties of p53-dependent DNA repair target genes that can affect various levels of cytogenetic aberrations in chronic hepatitis B patients. The present study aimed to examine the frequency of chromosomal aberrations and the mitotic index in patients with chronic hepatitis B and their possible association with p53 gene exon 4 codon 72 Arg72Pro (Ex4+119 G>C; rs1042522) polymorphism. Fifty-eight patients with chronic hepatitis B and 30 healthy individuals were genotyped in terms of the p53 gene codon 72 Arg72Pro polymorphism by PCR-RFLP. A 72-h cell culture was performed on the same individuals and evaluated in terms of chromosomal aberrations and mitotic index. A high frequency of chromosomal aberrations and low mitotic index were detected in the patient group compared to the control group. A higher frequency of chromosomal aberrations was detected in both the patient and the control groups with a homozygous proline genotype (13 patients, 3 control subjects) compared to patients and controls with other genotypes [Arg/Pro (38 patients, 20 control subjects) and Arg/Arg (7 patients, 7 control subjects)]. We observed an increased frequency of cytogenetic aberrations in patients with chronic hepatitis B. In addition, a higher frequency of cytogenetic aberrations was observed in p53 variants having the homozygous proline genotype compared to variants having other genotypes both in patients and healthy individuals.